Performance Evaluation of an ESPresense/MQTT Architecture for Real-Time Locating System - Vieira, Emanuel de Franceschi; Rizzetti, Tiago Antônio (Anais da Escola Regional de Redes de Computadores (ERRC); 2025: Anais da XXII Escola Regional de Redes de ComputadoresDO - 10.5753/errc.2025.17688, 2025)
This work evaluates the performance of a Real-Time Location System (RTLS) based on low-cost and open-source technologies. The system uses ESP32 devices running the ESPresense firmware to detect Bluetooth Low Energy (BLE) advertisements and publish data through the MQTT protocol. The performance tests were conducted on a single locator device that is part of an existing system deployed in a real environment, where multiple locators are distributed across different rooms. The results indicated an average latency of approximately 85 ms under low traffic and around 44 ms under continuous traffic, both with 0% message loss and stable response times. Furthermore, the throughput increased almost linearly with the number of active beacons, showing that the ESP32 did not become a processing bottleneck within the evaluated limits. These findings demonstrate that the ESPresense/MQTT architecture provides adequate performance, robustness, and scalability for medium-sized RTLS deployments at low cost.